2017
DOI: 10.1159/000485874
|View full text |Cite
|
Sign up to set email alerts
|

High Phosphate-Induced Calcification of Vascular Smooth Muscle Cells is Associated with the TLR4/NF-κb Signaling Pathway

Abstract: Background/Aims: Hyperphosphatemia is one of the most notable features of chronic kidney disease (CKD). Numerous epidemiological and clinical studies have found that high serum phosphate concentrations are associated with calcification in the coronary arteries. However, the mechanisms underlying the vascular calcification induced by high phosphate have not been understood fully. Methods: Vascular smooth muscle cells (VSMCs) were cultured in highphosphate media to induce vascular calcification, which was detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 43 publications
(41 reference statements)
0
48
0
Order By: Relevance
“…NF‐κB is a key transcription factor involved in diverse biological processes, which is recognized as a pivotal regulator of cell proliferation, differentiation, apoptosis, inflammation and so forth (Almaden et al, ; Viatour et al, ; Weng & Koh, ). Recent studies have demonstrated that NF‐κB has profound functions on the pathogenesis of VC by regulating the VSMC osteogenic transformation (Zhang et al, ; Zhao et al, ). Thus, we speculate that NF‐κB may also play a critical role in the IS‐induced VC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NF‐κB is a key transcription factor involved in diverse biological processes, which is recognized as a pivotal regulator of cell proliferation, differentiation, apoptosis, inflammation and so forth (Almaden et al, ; Viatour et al, ; Weng & Koh, ). Recent studies have demonstrated that NF‐κB has profound functions on the pathogenesis of VC by regulating the VSMC osteogenic transformation (Zhang et al, ; Zhao et al, ). Thus, we speculate that NF‐κB may also play a critical role in the IS‐induced VC.…”
Section: Discussionmentioning
confidence: 99%
“…It has been identified as a central regulator of gene expression associated with cell proliferation, differentiation, immunity and inflammation (Almaden et al, ; De Silva, Silva, Anderson, Bhagat, & Klein, ; Viatour, Merville, Bours, & Chariot, ). Recent studies have shown that activation of NF‐κB is expressed at a higher level in calcified vessels and inhibition of NF‐κB eliminates the Pi or TNF‐induced VSMC calcification in vitro (He et al, ; Zhang et al, ; Zhao et al, ; Zhao et al, ), suggesting that NF‐κB may also play a crucial role in the pathological of VC in CKD patients. Recently, numerous studies have reported that IS stimulated the activation of NF‐κB in various cells involved in the vessel senescence, endothelium dysfunction, and neuroinflammation (Adelibieke, Shimizu, Muteliefu, Bolati, & Niwa, ; Adesso et al, ; Shen et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Now, it is believed that vascular calcification involves a tightly regulated transformation of vascular smooth muscle cells to an osteo/chondrocytic cell that expresses Runt-related transcription factor 2 (Runx2) and produces matrix vesicles under hyperphosphate circumstance [26][27][28][29]. Recently, Chen [30], et al reviewed that high mobility group box 1 have a series of pro-calcification effects, such as promoting vascular smooth muscle osteo/chondrogenic differentiation, apoptosis and release of calcific extracellular vesicles, inflammation, oxidative stress and autophagy signaling, these indicated that inhibition of high mobility group box 1 may be a potential therapy for attenuating vascular calcification.…”
Section: Discussionmentioning
confidence: 99%
“…These matrix vesicles provide sites for further calcification. High-phosphorus stimulation increases the secretion of matrix vesicles, thereby aggravating vascular calcification [22, 23]. …”
Section: Discussionmentioning
confidence: 99%